The Effect of Using Fennel Seeds (Foeniculum vulgare L.) on Productive Performance of Broiler Chickens - Mohammed, Abdullah A.; Abbas, Rabia J. (International Journal of Poultry Science, 2009)
An experiment was conducted at the College of Agriculture Poultry Farm, University of Basra from 20/11/2007 to 2/1/2008 to study the effect of adding fennel seeds to the diet on productive performance of broiler chickens. A total of 120 day - old chicks were randomly distributed into four dietary treatments of fennel 0, 1, 2 and 3 g/kg diet contained 36% and 32% chick peas in the starter and finisher diets respectively. Results indicated that there was a significant improvement (p<0.05 ) in final body weight and feed efficiency. Carcass characteristics had no significant differences except true stomach and pancreas weight percentage. Flier repletion was highly significant when fennel was added. However chicks fed 1, 2 and 3 g/kg fennel had significantly (p<0.05) higher red blood cells, hemoglobin and packed cell volume. Hetrophil to lymphocyte ratio was significantly (p<0.05) declined for the chicks received 2 and 3g/kg fennel.